Growth and Yield of Kalimantan Landrace Rice and “IPB 8G” as Affected by Dose and Time of Application of Nitrogen Fertilizer - Faisal, Faisal; Lubis, Iskandar; Junaedi, Ahmad; Sugiyanta, Sugiyanta (Department of Agronomy and Horticulture, IPB University, 2019)
The study aimed to determine the effect of nitrogen fertilizer dose and the frequency of application on the growth and production of landrace rice Kalimantan and a new rice cultivar